Kualitas Pelayanan Administrasi Kependudukan Di Kota Banjar Tahun 2024 - Euis Ratna Sari; Asep Nurwanda; Irfan Nursetiawan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study is motivated by the suboptimal quality of population administration services at the Department of Population and Civil Registration (Disdukcapil) of Banjar City. The purpose of this research is to describe and analyze the quality of administrative services in Banjar City. The method used is descriptive qualitative. The results show that in the tangible dimension, obstacles include limited facilities and infrastructure such as frequently damaged document printers, insufficient computers, narrow waiting areas, and lack of disability-friendly facilities. Efforts made include procuring new equipment, regular maintenance, and improving service space. In the reliability dimension, there are inconsistencies in procedures and information discrepancies among officers. Disdukcapil addresses these by providing staff training, improving the digital information system, and increasing public outreach. In the responsiveness dimension, the main issue is the lack of personnel during peak service periods. Solutions include staff additions, work pattern restructuring, and cross-functional training. The assurance dimension shows generally good service, though challenges remain in maintaining service speed. Disdukcapil strengthens internal supervision and implements digital queuing systems. In the empathy dimension, services are delivered with care, friendliness, and without discrimination. The public feels respected and personally assisted during the service process.